Xyloglucan processing machinery in Xanthomonas pathogens and its role in the transcriptional activation of virulence factors - Plinio S. Vieira (Nature Portfolio, 2021)
Xyloglucans are polysaccharides found in plant cell walls. Here, the authors describe the xyloglucan depolymerization machinery of phytopathogenic Xanthomonas bacteria, and show that sugars released by this system induce the expression of key virulence factors driving pathogenesis.